Socio-Economic Characteristics of Community Around the Residental Complex in Campus Area of West Aceh District, Aceh Province - Wahyuningsih, Yayuk Eko; Zulham, T.; Ansari, Leli Putri; Ujung, Sahna Wati Br (Teunuleh Publisher, 2023)
The shift in the status of certain investments, such as the transition from private institutions to public ones, has a significant impact on enhancing the socio-economic landscape of a region. This transformation is evident in the southwest coast of Aceh, particularly in West Aceh District, where two private universities (Teuku Umar University and STAIN Meulaboh) were converted into state institutions, accompanied by the establishment of AKN Aceh Barat, a new state campus. This study aims to assess the social and economic characteristics of residents in housing complexes near West Aceh District's campus cluster in Aceh Province. The primary data for this study were collected from five points within these housing complexes, including Perumnas Alps, ADB Complex I and II, Griya Mahoni Housing, and Sanggamara Housing. A total of 100 households were surveyed using a simple random sampling method, and supplementary data were obtained from secondary sources. The findings indicate that, socially, a significant portion (22%) of residents in these housing complexes are civil servants, mainly working as lecturers or staff at the three campuses or nearby elementary and secondary schools. From a cultural perspective, 89% of the residents’ hail from Aceh, while 3% come from North Sumatra. Economically, the majority (38%) have a monthly income ranging from IDR 2,000,000 to 4,000,000, while 36% earn below IDR 2,000,000 per month. In conclusion, this research suggests the necessity for collaboration between the West Aceh District government, REI, and the three campuses to strategically plan new residential areas, fostering socio-economic advancement, and promoting environmental preservation through enhanced green initiatives.